Effect of synthesis parameters on the formation of zeolitic imidazolate framework 8 (ZIF-8) nanoparticles for CO2 adsorption - Lai, L.S. (Taylor and Francis Inc., 2014)
Zeolitic imidazole frameworks-8 (ZIF-8) is a subclass of metal-organic frameworks (MOFs) with the transition metal cations (Zn2+) linked by imidazolate anions forming tetrahedral frameworks in zeolite-like topologies. This article reports on the synthesis of ZIF-8 nanoparticles by varying the synthesis parameters at room temperature. The crystallization duration, molar ratios, and pH of the mixture solution were varied in order to study the effects of these parameters on the formation of ZIF-8 nanoparticles. The structural and morphology transformation of the resultant particles were characterized using x-ray diffraction, field emission scanning electron microscopy, and Brunauer-Emmett-Teller (BET) surface analysis. The CO2 adsorption characteristics of ZIF-8 nanoparticles were tested using CO2 physisorption analysis. Mature structural evolution was observed for ZIF-8 synthesized at 60 and 1440 min, but insufficient crystallization was found for ZIF-8 synthesized at 5 min. Meanwhile, ZIF-8 nanoparticles synthesized under lower amount of methanol resulted in larger particle size and higher crystallinity. Poorly intergrown ZIF-8 nanoparticles were observed for samples synthesized using a mixture solution with pH 8.2. Although different particle sizes and relative crystallinities were obtained for the ZIF-8 samples, synthesis using different molar ratios of the mixture solution, insignificant variations of BET surface areas, and CO2 adsorption capacities were found. Â© 2014 Taylor & Francis Group, LLC.